Development of Digital Comic Media to Prevent Bullying in Early Childhood - Faridah Rahmah; Alpino Susanto; Albert Efendi Pohan; Hamjah Hamjah; Mahmud Mahmud (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2026)
This study aims to produce a Batam Malay culture-based digital comic media that is feasible, practical, and effective in preventing bullying in early childhood. This research adopted a Research and Development (R&D) framework using the ADDIE model, comprising the stages of analysis, design, development, implementation, and evaluation. The digital comic was developed using the Ibis Paint X application and tested with 60 children aged 5–6 years at TK Victoria Batam. The data collection techniques included expert feasibility questionnaires, teacher and parent practicality questionnaires, and pretest and posttest observations of children’s empathetic behavior. The research results showed that the digital comic media had a feasibility level of 91.42%, categorizing it as very feasible. The practicality assessment by teachers and parents reached 94.61% and 91.76%, respectively, with a very practical category. In addition, the effectiveness test results showed an N-Gain of 82, indicating a high category. Thus, the Batam Malay culture-based digital comic media was stated to be feasible, practical, and effective as a character education tool in preventing bullying in early childhood